Brain Functional Changes before, during, and after Clinical Pain. (May 2018) - Hu, X.; Racek, A.J.; Bellile, E.; Nascimento, T.D.; Bender, M.C.; Toback, R.L.; Burnett, D.; Khatib, L.; McMahan, R.; Kovelman, I.; Ellwood, R.P.; DaSilva, A.F.
This study used an emerging brain imaging technique, functional near-infrared spectroscopy (fNIRS), to investigate functional brain activation and connectivity that modulates sometimes traumatic pain experience in a clinical setting. Hemodynamic responses were recorded at bilateral somatosensory (S1) and prefrontal cortices (PFCs) from 12 patients with dentin hypersensitivity in a dental chair before, during, and after clinical pain. Clinical dental pain was triggered with 20 consecutive descending cold stimulations (32° to 0°C) to the affected teeth. We used a partial least squares path modeling framework to link patients' clinical pain experience with recorded hemodynamic responses at sequential stages and baseline resting-state functional connectivity (RSFC). Hemodynamic responses at PFC/S1 were sequentially elicited by expectation, cold detection, and pain perception at a high-level coefficient (coefficients: 0.92, 0.98, and 0.99, P < 0.05). We found that the pain ratings were positively affected only at a moderate level of coefficients by such sequence of functional activation (coefficient: 0.52, P < 0.05) and the baseline PFC-S1 RSFC (coefficient: 0.59, P < 0.05). Furthermore, when the dental pain had finally subsided, the PFC increased its functional connection with the affected S1 orofacial region contralateral to the pain stimulus and, in contrast, decreased with the ipsilateral homuncular S1 regions ( P < 0.05). Our study indicated for the first time that patients' clinical pain experience in the dental chair can be predicted concomitantly by their baseline functional connectivity between S1 and PFC, as well as their sequence of ongoing hemodynamic responses. In addition, this linked cascade of events had immediate after-effects on the patients' brain connectivity, even when clinical pain had already ceased. Our findings offer a better understating of the ongoing impact of affective and sensory experience in the brain before, during, and after clinical dental pain.